2005
DOI: 10.1051/0004-6361:20047021
|View full text |Cite
|
Sign up to set email alerts
|

The radio–ultraviolet spectral energy distribution of the jet in 3C 273

Abstract: Abstract. We present deep VLA and HST observations of the large-scale jet in 3C 273 matched to 0. 3 resolution. The observed spectra show a significant flattening in the infrared-ultraviolet wavelength range. The jet's emission cannot therefore be assumed to arise from a single electron population and requires the presence of an additional emission component. The observed smooth variations of the spectral indices along the jet imply that the physical conditions vary correspondingly smoothly. We determine the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(133 citation statements)
references
References 44 publications
8
124
1
Order By: Relevance
“…In 3C 273, Jester et al (2005) have already shown that only knots A and B1 have X-ray indices similar to their radio indices (which is required for IC/CMB), so our "combined knot" scenario includes only these two knots. For PKS 0637-752, we use all the bright X-ray knots just before the turn in the jet (wk7.8, wk8.9, wk9.7, and wk10.6) where one might assume that some deceleration likely takes place.…”
Section: Results: Testing the Ic/cmb Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…In 3C 273, Jester et al (2005) have already shown that only knots A and B1 have X-ray indices similar to their radio indices (which is required for IC/CMB), so our "combined knot" scenario includes only these two knots. For PKS 0637-752, we use all the bright X-ray knots just before the turn in the jet (wk7.8, wk8.9, wk9.7, and wk10.6) where one might assume that some deceleration likely takes place.…”
Section: Results: Testing the Ic/cmb Modelmentioning
confidence: 98%
“…We have also measured updated radio fluxes based on a re-analysis of archival and new ATCA data at 4.8, 8.4, and 17.8 GHz (first published in Godfrey et al 2012b). For 3C 273, data is taken from Jester et al (2005Jester et al ( , 2006 and Uchiyama et al (2006) and references therein.…”
Section: Results: Testing the Ic/cmb Modelmentioning
confidence: 99%
“…Left: Knot A in 3C 273 jet in radio and optical frequencies (from Jester et al 2005). Right: Different components of the knot K25 in 3C 120 jet in X-ray frequencies (from Harris et al 2004).…”
Section: Figurementioning
confidence: 99%
“…For a recent review of KHI in YSO jets see the article by Trussoni (2009). While radiative cooling is not thought to be important on the relativistic jets there are still some interesting similarities in morphology between YSO jets and AGN jets, e.g., compare the knots, twists, asymmetries and bow shock structures in HH 212 (Zinnecker et al 1998) and HH 111 (Reipurth et al 1997;Reipurth et al 1999) with the knots and twists in 3C 273 (Jester et al 2005;Uchiyama et al 2006) and the twists and bow shock structures in Hercules A (Dreher & Feigelson 1984). Thus, the following discussion restricted to nonradiative KHI and CDI work will also be relevant to the YSO jets.…”
Section: Introductionmentioning
confidence: 99%